When gossips meet women, family, and neighbourhood in early modern England - Capp, B. S. (Oxford studies in social history., 2003)
Aimed at social and cultural historians, this is an exploration of how women of the poorer and middling sorts in early Modern England negotiated a patriarchal culture. It focuses on the networks of close friends ('gossips') which gave them a social identity beyond the narrowly domestic.